Nivel de estrés y el rendimiento académico en estudiantes de subnivel medio y superior. - Muñoz, Irving M. (2022)
The objective of the study is to estimate the level of stress and the academic performance of the students of the "Rumipamba" Educational Unit of the middle and higher sublevel, the problem is that stress is an invisible element that affects the development of skills. and abilities of the students, reflected in their academic performance, is not seen as a problem by the teacher, because the term stress is confused with tiredness, exhaustion or fear. The methodology is centered on the quantitative paradigm, the study is descriptive and field. The MBI-SS Test, Maslach Burnout Inventory-Human Services Survey, was applied to students, in the dimensions, emotional exhaustion, depersonalization and academic efficacy of 172 students of middle and higher sublevel of the Rumipamba Educational Unit of the city of Ibarra. The results showed a strong relationship between stress and academic performance, the application of a Chi Square Test with 5% degrees of freedom and α = 15, showed a very short difference between the expected and calculated result of 27.39 for Exhaustion emotional, and 26.4 for Depersonalization, considered as a strong relationship, and a weak relationship of 25.12 in Academic Efficacy. It is concluded that the majority of students suffer from high-level stress, in addition to having low academic performance, variables that are significantly related.